The social life of emotive interjections in spoken British English - Stange, Ulrike (Scandinavian Studies in Language, 2019)
This paper explores the discursive use of selected emotive interjections (Ow!, Ouch!; Ugh!, Yuck!; Whoops!, Whoopsadaisy!) in spoken British English. The data (drawn from the Spoken BNC2014) are coded for age, gender, social grade and type of dyad to identify potential factors governing the discursive use of these interjections. Based on 140 relevant tokens, the results suggest that: 1) The individual interjections vary significantly regarding how frequently they are found in discursive uses (p<0.001***). 2) Whoopsadaisy! is not attested in discursive uses. 3) Young female speakers behave differently from the other speaker groups in that they use emotive interjections discursively significantly more frequently (p=0.006***). 4) Female speakers in general use a wider range of interjections discursively: Ow! and Whoops! in discursive uses were absent from male speech. 5) Socio-economic status is irrelevant, as is 6) type of speaker dyad. Thus, the social life of emotive interjections is mainly influenced by speaker gender, and if the speakers are female, also by their age.